NEUROPROTECTIVE EFFECTS OF MEDICINAL PLANTS IN ALZHEIMER’S DISEASE AND PARKINSON’S DISEASE (Cuestiones de Fisioterapia, 2025)
Neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease (PD) are characterized by progressive neuronal loss, cognitive decline, and motor dysfunction. Current therapeutic strategies primarily focus on symptom management rather than disease modification. Medicinal plants have gained significant attention due to their neuroprotective properties, which include antioxidative, anti inflammatory, anti-amyloidogenic, and cholinesterase-inhibitory effects. Various phytochemicals, including flavonoids, alkaloids, and polyphenols, have shown potential in mitigating neurodegenerative processes by targeting oxidative stress, mitochondrial dysfunction, and neuroinflammation. This review explores the molecular mechanisms underlying the neuroprotective effects of medicinal plants, with a focus on key herbs such as Ginkgo biloba, Curcuma longa, Withania somnifera, Bacopa monnieri, and Camellia sinensis. Furthermore, it discusses preclinical and clinical studies supporting their efficacy, limitations, and future research directions in neurodegenerative therapy.